Interaction of Warfarin with Herbs Based on Pharmacokinetic and Pharmacodynamic Parameters - Amelia Soyata; Aliya Nur Hasanah; Taofik Rusdiana (Indonesian Journal of Pharmaceutics, 2020)
Warfarin is an oral anticoagulant that has been widely used and has strong efficacy, but the use of warfarin is still a concern because of its narrow therapeutic index which cause interactions when co-administration with drugs, herbs or food. This interaction can affect the pharmacokinetics and pharmacodynamics of warfarin and the most fatal effect from warfarin interactions is bleeding. In this review article data on warfarin-herbs interactions were collected based on pharmacokinetic parameters (AUC0-∞, Cmax, T1/2, Cl/F, and V/F), while pharmacodynamic parameters (International normalized ratio (INR), platelet aggregation, AUC INR and Protombine Time). As a result some herbs had significant interactions with warfarin. Herbs that affect warfarin pharmacokinetic were Danshen gegen, echinacea, St. John's wort and caffeine and herbs that affect pharmacodynamic were policosanol, Ginkgo biloba, cranberry, St. John's wort, ginseng, pomegranate, Psidium guajava and curcumin, so co-administration warfarin with herbs need to be considered.Keywords: Warfarin, Interactions, Herbs, Pharmacokinetics, Pharmacodynamics